P‐141: Sub‐millisecond Switching of Vertically‐Aligned Liquid Crystals Aided by Two‐Dimensional Confinement with Virtual Walls. Issue 1 (30th May 2018) - Choi, Tae-Hoon; Jeon, Byoung-Gyu; Woo, Jae-Hyeon; Yoon, Tae-Hoon
Abstract : We report approaches for sub‐millisecond switching of vertically‐aligned nematic liquid crystals (LCs). When an in‐plane field is applied to a vertical alignment (VA) cell, virtual walls are built at the center of the interdigitated electrodes and at the middle of the gaps between them. The LC molecules are confined not only by the two substrates but also by the virtual walls so that the turn‐off time of a VA cell driven by an in‐plane field is dependent on the pitch of the interdigitated electrodes as well as the cell gap. Therefore, the turn‐off time of a VA cell driven by an in‐plane field can be reduced simply by decreasing the pitch of the interdigitated electrodes as a result of the enhanced anchoring provided by the virtual walls. We experimentally obtained a sub‐millisecond response time in the VA cell. The measured turn‐on and turn‐off times of the fabricated VA‐FFS cell was 0.33 ms and 0.41 ms, respectively.